The Effect of Audit Quality, Audit Committe and External Audit on Financial Reporting Quality: Empirical Study of Registered Real Estate Companies in Indonesia Stock Exchange - Sulbahri , Rifani Akbar; Putri, Yuni Adinda; Susanti, Mulyani (Jurnal Keuangan dan Bisnis, 2021)
This research discuss the effect of the quality of audit, audit committe, and external audit on financial reporting quality registered real estate companies in Indonesia Stock Exchange (BEI). The population in this research are property and real estate companies listed on the Indonesia Stock Exchange from 2014-2017 with the observation period annual financial report issued by using 27 sample companies that match the criteria set by author with purposive sampling method. The data was tested by using classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study show that: a) Simultaneously the quality of audit, audit committe and external audit has a significant effect on the quality of financial reporting; b) Partially, audit quality does not have a significant effect on the quality of financial reporting; c) Partially the audit committee does not have a significant influnce on financial reporting quality, and d) Partially the external audit has a significant effect on the quality of financial reporting. It is better for the next researcher to add other variables besides audit quality, audit committee, and external audit to financial reporting quality.